Effect of support on molybdenum oxide acidity for n-heptane isomerization - Abdul Fatah, Nor Aiza (Penerbit UTM Press, 2016)
Skeletal isomerization of alkanes into the corresponding branched isomers has attracted many attentions as a reaction to produce clean fuel with high octane quality. In this study, molybdenum oxide (MoO3) catalyst supported on mesostructured silica nanoparticles (MSN), HZSM-5 and MCM-41 activity were being tested towards n-heptane isomerization at 623 K. The catalyst acidity was characterized by using FTIR pre-adsorb pyridine. The results showed that MoO3-MSN possesses highest Lewis acid and lowest Brönsted acid concentrations. The catalytic testing towards n-heptane isomerization showed that MoO3-MSN exhibited the highest n-heptane conversion of 18.7 % at 623 K. It was suggested that the high Lewis acid in the MoO3-MSN may facilitate the formation of active protonic acid sites from molecular hydrogen through hydrogen spillover mechanism and hence improves the n-heptane conversion.